Development of a Timetabling Software Using Soft-computing Techniques With a Case Study - Sabri, M.F.M.; Husin, M.H.; Chai, S.K. (IEEE, 2010)
Timetabling is the assigning of an event to a particular timeslot in a timetable. Timetabling becomes a problem when the assigning task becomes hard to be implied where certain specific requirements need to be fulfilled. Genetic Algorithm (GA) emerge as one automation timetabling method to solve timetabling problem by searching solution in multi-points and the ability to refine the existing solution to a better solution. The timetabling program is specifically designed and developed in MATLAB programming language based on simple GA method to solve the timetabling problem for the case study. The developed timetabling program hardly found a good timetable solution as the solution finding converges at one point. Result shows the simple GA is not applicable in timetabling problem with high constraints and limited free slots.